Phosphorylation of connexin in functional regulation of the cardiac gap junction - Imanaga, Issei (Pulsus Group Inc, 2004)
In cardiac muscle, the gap junction contributes to electrical cell-to-cell coupling. This physiological function of the gap junction depends on the phosphorylation state of the connexin molecule, which comprises the gap junction channel. The effects of intracellular Ca(2+) overload, acidosis, activation of protein kinase (PK) A, PKC and PKG on the phosphorylation and expression of connexin 43 (Cx43) were examined in animal hearts with reference to physiological function. Activation of PKA promotes cell-to-cell coupling due to augmentation of the PKA-mediated phosphorylation of Cx43, with a rise in the quantity of and an increase in the expression of Cx43. A rise in the ionic strength of Ca(2+) and H(+) impaired cell communication, with the inhibition of PKA-mediated Cx43 phosphorylation. Activation of PKC reduces the quantity and expression of Cx43 despite augmentation of PKC-mediated phosphorylation of the protein. The effects of PKG activation are similar to those of PKC activation. It is suggested that PKA activation upregulates and PKC activation downregulates Cx43. The role of connexin phosphorylation in the regulation of gap junction function is discussed.